Survey of Relation between Computer Anxiety with Academic Achievement, Self Esteem and Gender of veterans Students in Tehran: 2011 - L. Sarabadani; A. Bolvardi; M. Ghiasi (Afarand Scholarly Publishing Institute, 2012)
Background: Computer Anxiety can be caused to learning disorders in students that attention to this issue has a main role for health and knowledge improvement in veteranchr('39')s students. Purpose: the purpose of this study was to survey of the relationship of academic achievement, self-esteem and gender of graduate of veteranchr('39')s students with their computer anxiety in Tehran Universes on 2011. Methods & Materials: The type of this study was descriptive analyses that sample consisted of 200 randomly selected students, Data after collecting with questioner was analyzed by Correlation coefficient and Multiple Regression Analysis. Results: The result among 200 students showed that there was a significant negative relationship between self esteem and computer anxiety of students r= -0/358 also was a significant relationship between achievement motivation r= -0/252. Conclusion: Self-esteem is a good predictor of computer anxiety that this can be a guide line for social and cultural policymaker in decrease of study problems for veteran students on country. Key Words: Computer Anxiety, veteran, Tehran